Mathematical Vindication of Ricardo on Machinery - Samuelson, Paul A. (Journal of Political Economy, 1988)
Ricardo is shown to be right that machinery can hurt wages and reduce output. A dramatic robot example reveals Wicksell's error in believing that Pareto optimality calls for no drop in total output from a viable invention. Under Ricardo's axiom that labor supply adjusts to keep wages at the subsistence level, he can correctly deduce on a market-clearing basis a rise in his net product (rent plus interest), while the greater drop in population and total wages result in a reduction in his gross product (rent plus interest plus wages).